Pensamiento bioético de Fidel Castro Ruz : vigencia en el modelo formativo de la salud cubana - Rodríguez García, Manuel de Jesús; García Raga, Mónica; Rodríguez Suárez, Carlos Manuel (Revista 16 de abril, 2018)
The bioethics like indispensable science for the humanity’s sustenance find in Fidel Castro Ruz a legitimate exponent with a genuine impression in the formative pattern of the Cuban health. Areview study of update bibliographical sources that allowed to select 22 illustrative referents of the thematic one was performed, with the objective of characterizing Fidel Castro Ruz’s bioethics think and their contribution to the contemporary bioethics and the formative pattern of the Cuban health. As theoretical method the historical-biographical one was used, by means of the analysis-synthesis application, induction-deduction and historical-logical focus. The results of the investigation notice that the characteristics of Fidel Castro Ruz’s bioethics thinkdignify a new model of society and they are preceded to the epistemological paradigm of their time, as expression of the highest grade of humanism to universal scale that impacts in an explicit way in the formative pattern of the Cuban health.